SURVAI PENGEMBANGAN PROGRAM BIMBINGAN DAN KONSELING (BK) DI SEKOLAH - Atrup, Atrup (Universitas Nusantara PGRI Kediri, 2014)
Paradigm shift in guidance and counseling (G&C) should be understood and implemented in development and programming G&C at school. But in reality, not all of the teachers understand and implement it. This study aimed to describe the types of development and forming models (patterns), also the reasons why G&C teachers (school counselor) choose the model. This was the survey research, the data obtained through document reports by students that surveyed on the implementation of the school counseling program. There were 22 reports which analyzed and the results were summarized as follows: (1) Many of G&C teachers developed and programmed G&C based on the pattern of 17 and 17+ (86.36%) and only slightly (13.63%) was based on Kerangka Kerja Utuh (KKU), (2) The reasons of using the pattern of 17 and 17+ was because they do not understand the concept, procedures and implementation of KKU models. It means they do not follow G&C paradigm well.